Teachers’ Competence in Implementing Thematic Social Studies Instruction: An Evaluative Study at Junior High School Level of Lumajang Regency - Sutomo, Moh.; Musyarofah; Arifin, Miftah (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikdasmen, 2025)
The effective implementation of thematic learning in Social Studies (IPS) at the junior secondary level requires teachers to possess interdisciplinary knowledge and advanced pedagogical skills. This study explores competency gaps among Social Studies teachers without formal Social Sudies qualifications in Lumajang Regency, Indonesia, and examines how these gaps affect thematic learning delivery. Using a qualitative phenomenological approach, data were collected through non-participant observations, structured questionnaires, and in-depth interviews with 30 teachers from SMP and MTs schools. The findings reveal significant disparities in subject matter expertise, instructional design, and classroom management, with only 50% of teachers meeting competency standards for thematic Social Studies teaching. Key factors underlying these gaps include diverse academic backgrounds, limited understanding of the thematic curriculum, and insufficient engagement in professional development activities. The study highlights the urgent need for targeted capacity-building programs, continuous professional learning opportunities, and collaborative teacher networks to bridge competency deficiencies. Furthermore, policy interventions are recommended to standardize teacher qualifications and support sustained professional growth. Addressing these challenges can improve the quality of thematic Social Studies instruction and improve student learning outcomes. This study provides an empirical foundation and policy recommendations for improving teacher competence within the context of an integrated curriculum which can be utilized by education stakeholders in Indonesia and in similar settings.